Issues for infrastructure management in the 1990s - Israel, Arturo (World Bank WashingtonUS, 1992)
Looks at infrastructure as a whole. Reviews recent developments, highlights new insights emerging from subsectoral or country comparisons, illustrates successful approaches, and proposes a number of measures aimed at increasing the productivity of infrastructure services.